2020
DOI: 10.24912/jmieb.v4i2.8381
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Brand Image, Halal Label, and Halal Awareness on Customers Purchasing Decision of Halal Cosmetic

Abstract: Kosmetik adalah elemen penting untuk kehidupan sehari-hari dan telah menjadi gaya hidup, terutama bagi wanita. Penggunaan kosmetik harus mematuhi peraturan keamanan pemerintah. Wardah adalah merek kosmetik yang dirancang dengan pengetahuan lokal dan berbahan alami. Wardah menerima Penghargaan Top Trademark Halal dalam kategori kosmetik, namun dari pra-survei terhadap Muslim milenial, terdapat 52,6% responden tidak mempertimbangkan label halal dalam pembelian produk kosmetik. Tujuan dari penelitian ini adalah u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 0 publications
3
15
0
6
Order By: Relevance
“…Looking into the scenario of purchasing halal products, individuals might consider some relevant factors (for example food safety, cleanliness, certification, prices) and assess producers for their ability, before continuing to buy halal food products. The halal logo can offer some security or guarantee, has more value and is more important than ISO or similar certification for the perception of all customers (Genoveva & Utami, 2020;Kartika, 2020;Osman et al, 2019;Simbolon, 2019). The reliability of the product shows more quality than nonhalal products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking into the scenario of purchasing halal products, individuals might consider some relevant factors (for example food safety, cleanliness, certification, prices) and assess producers for their ability, before continuing to buy halal food products. The halal logo can offer some security or guarantee, has more value and is more important than ISO or similar certification for the perception of all customers (Genoveva & Utami, 2020;Kartika, 2020;Osman et al, 2019;Simbolon, 2019). The reliability of the product shows more quality than nonhalal products.…”
Section: Discussionmentioning
confidence: 99%
“…The focus of several previous studies only discusses the role of halal labels as an influence in purchasing halal food. Most of the halal labels are indicators of decisions, but do not explain in detail what aspects are behind individuals in making decisions (Genoveva & Utami, 2020;Kartika, 2020;Osman et al, 2019;Simbolon, 2019). While this research focuses on studying 14,1 the psychology of the general public, in making purchasing decisions.…”
Section: Problem Statement and Objectivementioning
confidence: 99%
“…A halal label must be the main thing to consider for someone with a high religious value before buying a product. This study is relevant to research conducted by (Genoveva & Utami, 2020;Mohezar et al, 2016;Öztürk, 2022) which revealed that halal labels are components consumers will see when buying a product.…”
Section: Halal Labelmentioning
confidence: 99%
“…Studies related to consumer preferences for purchasing decisions for cosmetic products have been widely studied by previous researchers using attitude factors (Aisyah, 2016;Handriana et al, 2020); halal awareness (Genoveva & Utami, 2020;Mufrodah & Adinugraha, 2021;Sholikhah et al, 2021); religiosity (Choiriyah & Damayanti, 2020;Mohezar et al, 2016;Riwajanti et al, 2020); subjective norms (Aisyah, 2016;Kamaruddin et al, 2012); knowledge (Riwajanti et al, 2020;Sholikhah et al, 2021), halal label/logo/certificate (Choiriyah & Damayanti, 2020;Genoveva & Utami, 2020;Mohezar et al, 2016) and loyalty (Mufrodah & Adinugraha, 2021). In addition, we analyzed the variables generally studied in halal cosmetic products, including religiosity, halal certification, attitudes, awareness, and intention to buy halal cosmetic products.…”
Section: Introductionmentioning
confidence: 99%
“…High dissatisfaction will then lead someone to regret (Chang et al, 2014). Furthermore, the brand image is a combination of memories about the brand of the product (Genoveva and Utami, 2020). Good brand image means that all about the product is positive.…”
Section: Dissatisfaction and Brand Image As Causal Variablesmentioning
confidence: 99%